2021
DOI: 10.3390/hydrogen2030018
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Jet Fire from a Thermally Activated Pressure Relief Device (TPRD) from Onboard Storage in a Naturally Ventilated Covered Car Park

Abstract: Hydrogen jet fires from a thermally activated pressure relief device (TPRD) on onboard storage are considered for a vehicle in a naturally ventilated covered car park. Computational Fluid Dynamics was used to predict behaviour of ignited releases from a 70 MPa tank into a naturally ventilated covered car park. Releases through TPRD diameters 3.34, 2 and 0.5 mm were studied to understand effect on hazard distances from the vehicle. A vertical release, and downward releases at 0°, 30° and 45° for TPRD diameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Another article indicated that inside a tunnel, the size of the flammable vapor cloud decreases with increasing wind strength yet remains unchanged beyond a certain wind speed [12]. Furthermore, a study investigating the risks in indoor spaces following jet flame generation due to the operation of a TPRD in hydrogen vehicles parked in compartmentalized underground spaces indicated that maintaining the TPRD outlet angle at 45 • or less was safer [13]. This orientation minimizes the risk to passengers during rescue operations, as jet flames discharged perpendicular to the floor pose greater hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Another article indicated that inside a tunnel, the size of the flammable vapor cloud decreases with increasing wind strength yet remains unchanged beyond a certain wind speed [12]. Furthermore, a study investigating the risks in indoor spaces following jet flame generation due to the operation of a TPRD in hydrogen vehicles parked in compartmentalized underground spaces indicated that maintaining the TPRD outlet angle at 45 • or less was safer [13]. This orientation minimizes the risk to passengers during rescue operations, as jet flames discharged perpendicular to the floor pose greater hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Much research is being conducted on ensuring the safety of hydrogen facilities and equipment, such as hydrogen tanks and hydrogen refueling stations [10][11][12]. Hussein et al investigated temperature variations in the release direction of a jet flame in a parking area and found that it was difficult for passengers to escape when the jet flame was released vertically [13]. Accidents that can occur in hydrogen passenger vehicles include leaks, jet flames, and explosions, but the one most likely to cause damage is a sudden burst of flame from the activation of the TPRD.…”
Section: Introductionmentioning
confidence: 99%